PENGARUH LITERASI KEUANGAN, FINANCIAL ATTITUDEDAN INCOME TERHADAP PERILAKU MENABUNG(Survei Pada Karyawan Konveksi Generasi Z di Kota Tasikmalaya) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The purpose of this study is to understand the influence of financial literacy, financial attitude and income on saving behavior (survey on generation z convection employees in Tasikmalaya City). This study uses a quantitative causality method with a survey approach. The population taken in this study were generation z convection employees in Tasikmalaya City. With a research sample of 100 respondents. The technique for determining the sample in this study used non-probability sampling. Precisely using the purposive sampling technique. The data obtained in this study are primary and secondary data. The analysis tool used in this study is multiple regression using SPSS Version 25. Based on the results of the F test, it shows that financial literacy, financial attitude and income simultaneously have a significant effect on saving behavior. Based on the results of the T test, it shows that financial literacy partially has a significant effect on saving behavior. While financial attitude and income partially do not have a significant effect on saving behavior.